Apolipoprotein E Polymorphisms in Andean Population of Jujuy, Argentina - Trigo, Arturo Nicolas (2024)
The pleiotropic nature of the apolipoprotein E (APOE) gene is associated with complex diseases in different populations. We analyzed APOE polymorphisms in 76 individuals from Jujuy – Argentina using NGS technology. The observed genotypes align with the expected Hardy–Weinberg equilibrium. APOE3 was the most common allele, followed by APOE4 and APOE2. The allele distribution pattern is consistent with findings in previously studied populations of Native Americans and Asians. The E4 allele’s low frequency, always observed in a heterozygous state, raises questions regarding its relevance in explaining dementia and longevity associated with this marker in the Central Andes.